Oil spill remediation : colloid chemistry-based principles and solutions - Somasundaran, P., 1939-; Patra, Partha; Farinato, Raymond S.; Papadopoulos, Kyriakos, 1956- (Hoboken, New Jersey : Wiley, 2014)
In April of 2010, the Deepwater Horizon oil spill in the Gulf of Mexico became the largest accidental release of oil into marine waters in history, resulting in severe environmental, health and economic consequences. Begins with a science-based overview of the 2010 Deepwater Horizon oil spill. Next, it discusses: Oil spill remediation from the perspective of physicochemical and colloidal science; Current regulations on toxic impact of oil and dispersants, and the available environment assessment tools and resources for the remediation of oil spills; Current research on dispersants, colloids, and other options for remediation. Each chapter addresses deeper scientific problems associated with current technologies and highlights the urgent need for better remediation methods. This monograph is valuable for all experts in, but not limited to, the chemical, physical-chemical, geological and environmental fields, endeavoring to understand, design and develop new and efficient remediation techniques.--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Oil spills -- Cleanup; Oil pollution of water; Oil pollution of the sea; Emulsions; TECHNOLOGY & ENGINEERING -- Environmental -- General; Emulsions; Oil pollution of the sea; Oil pollution of water; Oil spills -- Cleanup; Electronic books; Electronic books